The translation of the French grammatical structure preposition 'sans + infinitive' within the novel by Boris Vian Foam of the Days - Bergerová, Lucie (Bohemica Olomucensia, 2012)
The article deals with a translation of the French grammatical structure preposition 'sans + infinitive' within the novel by Boris Vian Foam of the Days. The report provides basic information about the French language in terms of its typology, verbs, infinitive and semi-clause structures, the preposition "sans" in the structure 'preposition + infinitive'. Using the examples from Foam of the Days documents how these structures can be compensated.